Diglossia Situation of Javanese Deli Speakers In Hamparan Perak Districts Deli Serdang Regency - Tarihoran, Rezky Khoirina (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2024)
This research aims to explore the domains and variations of language use in the diglossia situation among Javanese Deli speakers in Hamparan Perak District, Deli Serdang Regency. A qualitative research method was employed, focusing on the Javanese Deli speakers in this region. The study found that diglossia occurs across several domains: family, social, professional, religious, and transactional. Each domain exhibits distinct diglossia characteristics. In the family domain, the use of a higher language variant is often influenced by the educational background of the family head. In social interactions, a lower language variant is used when speakers share the same ethnic background, particularly among Javanese Deli people. The religious domain sees the use of a higher variant, as the district is predominantly inhabited by Javanese, Deli, and Malay communities, making Indonesian the preferred language to avoid conflicts. In professional and transactional contexts, a lower variant is commonly used, with occasional shifts to a higher variant in informal situations. Overall, the study reveals that the lower language variant is more prevalent, supporting the preservation of the Javanese Deli language in Hamparan Perak District.